(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2018)
Background: Patients with gastric outlet obstruction, secondary to corrosive ingestion admitted in pediatric surgery department from January 2005 to June 2016. Most common corrosive was sulphuric acid and it was taken accidentally by pediatric groups. Besides this, hydrochloric acid, carbolic acid, sodium hydroxide, sodium hypochlorite, sodium carbonate etc are also common. Following conservative treatment, patients developed gastric outlet obstruction within 12 to 20 days. Surgery was performed to relief obstruction. Patients and Methods: Our study is a retrospective study on gastric outlet obstruction following corrosive ingestion. 8 patients were admitted in the department of pediatric surgery from January 2005 to June 2016. H/O of corrosive intake, nature, time, type of injury, treatment and period of development were gastric outlet obstruction were taken. For diagnosis of gastric outlet obstruction endoscopy & barium meal X-ray of upper GIT were done. Pre-operative fluid and electrolyte imbalances, anemia and malnutrition were corrected. Gut preparation was also done before operation. All patients were operated under endo-tracheal general anaesthesia. Post operative period were uneventful. Feedings were started on 5th to 6th POD by initially liquid, then gradually semisolid to normal. Post operative complications were recorded. Patients were discharged on 8th POD. All patients were followed up 6months to 1 year. During follow up general conditions of patients, serum albumin level, Hb%, and endoscopy of upper GIT were performed. Results: Total number of patients in our study was eight, Male-6 & Femal-2, mean age about 6 years, ranging from 3 to 10 years, and intake corrosive accidentally. Period of development of was gastric outlet obstruction about 15 days, range 12 to 20 days. Initially complications were odynophagia and dysphasia. But latter develop with gastric outlet obstruction within 12 to 20 days. Mean operative time 1.5 hours. Procedure was posterior gastro-jejunostomy. No significant post-operative complications were encountered. On follow-up, all patients were being well. General conditions, appetite, weight gain were better. No re-do operation were performed. Conclusions: Avoidable circumstances can be reduced by cautiousness in family as well as in every aspect of our community. Early surgical intervention gives excellent result. Gastro-jejunostomy is a very safe operation with minimum morbidity and excellent long-term outcome. Journal of Paediatric Surgeons of Bangladesh (2017) Vol. 8 (1): 24-27